Large-area transparent biocomposite films based on nanocellulose and nanochitin via horizontal centrifugal casting. (1st April 2022) - Hwang, Hyunbin; Jang, Seyeon; Jin, Jungho
Abstract: In this study, we introduce the horizontal centrifugal casting (HCC) process that enables centrifugal force-assisted, scalable production of large-area (10 in.) polymer composite films based on nanocellulose (CNF) and nanochitin (ChNF). The HCC employs a cylinder mold with its rotation pivot being in a horizontal posture to harness centrifugal force to help flatten the film being cast, from which polymer composite films with excellent uniformity and flatness can be reliably produced in the size of the lateral surface of the cylinder mold. The combination of centrifugal force and horizontal layout of cylinder mold can allow reliable fabrication of large-area self-standing films from both polymeric solution and/or suspension in a scalable and simple fashion, which is a task not readily achieved in common film-forming techniques, such as solvent casting and vacuum filtration. We demonstrate such reliability and versatility of the HCC process by fabricating typical biocomposite films out of both a solution blend of ChNF/silk fibroin and a colloidal suspension of CNF/nanoclay as well as investigating their processing-structure-property relation as an optically transparent composite film targeting for structural component for flexible green optoelectronics and fire-retardant film, respectively. Graphical abstract: Unlabelled Image